Seed germination and seedling growth of Brassica chinensis L. var. parachinensis (Bailey) Sinskaja (flowering white cabbage) - Ferreira, Wanessa Resende; Ranal, Marli A. (Pesquisa Agropecuaria Brasileira, 1999)
Brassica chinensis var. parachinensis was introduced in Brazil in 1992. This variety presents a high content of vitamin A and a short life cycle. Seeds were submitted to 24 treatments in laboratory conditions and 12 treatments in field conditions with the objective of evaluating the germination pattern and seedling growth. In laboratory conditions, seed germination was light independent and the germinability was reduced in 12% by the action of sodium hypochlorite scarification. Gibberellic acid, KNO3, mechanical scarification and stratification did not modify the germinability of the seeds (96-100%) neither the average time of germination (1-1.28 days) in relation to the control treatment. In field conditions the highest values of emergence (89.2-96.4%) and the highest rates of emergence velocity (14.2-17.4) occurred in soil with mineral fertilization, between 0.5 and 1.5 cm depth. Shorter average times of emergence were registered from 0.5 to 1.5 cm depth (2.90-3.97 days), for the three fertilizers tested (mineral fertilization, cattle manure, and chicken manure). Seedlings were sensitive to sodium hypochlorite with significant reduction of hypocotyl and primary root. Stratification of seeds by 24 hours stimulated growth of primary roots improving the establishment of seedling in the soil.
Keywords: Brassicaceae; germinability; vegetable